Collaboration between Elementary Schools and Community Agencies to Reduce Violence: Can It Work? - Kimberly Williams (Arizona State University, 2015)
School personnel at seven urban elementary schools in a high poverty area were surveyed to determine if a multi-faceted approach to school violence prevention (including a major emphasis on collaboration between community human service agencies and schools) was successful in reducing indicators of violence (bullying, fighting, gang involvement, and so forth). Using the Assessment of Risk Factors survey, during the year prior to implementation 2001 to gather pre-test data, and again during the summative year 2004, comparisons were made to determine if these programs had been successful in reducing violence in the schools from the perspective of school personnel. Implications for school-community collaborations will be discussed.